Analyse numerique d’une formulation mixte de Ia magnetostatique lineaire - Daveau, Christian (European Journal of Computational Mechanics, 2000)
/11 this paper. we study magnetostatic problem. We establish a mixed formulation in magnetostatics and we show that the problem is well-posed with Brezzi-Babuslw theory, an inf-sup condition is proved. A mixed Raviart-Thomasjinite element method of minimal order is used to approximate the continuous problem in H(div) x L2 . Numerical tests are implemented to validate the method. First, we consider a sphere in a homogeneous source field then a domain in which the permeability is not constant.